Форми національної державності України в 1917 - 1921 роки - Новіченко, А. В.; Novichenko, A. V. (Європейські перспективи. - 2021. - № 4. – С. 26-33, 2021)
Розглянуто події, які відбувались з 1917 по 1921 рр., коли український народ переживав досить тяжкі часи, які супроводжувались і національними рухами, зміною органів влади, економічними кризами, переходу до різних форм правління тощо, але всі ці перетворення були спрямовані на встановлення незалежності держави. Надано історико-правова характеристика формам націоналізації державності в період часу з 1917 по 1921 рр. Виділено позитивні та негативні аспекти їх ставлення, що можна застосувати при запровадженні партнерських відносин між поліцією та громадськістю, діяльність яких спрямована на підвищення рівня протидії кримінальним правопорушенням та охороні правопорядку.

The Ukrainian people in the period from 1917 to 1921 experienced quite difficult, but significant, for the further development and «prosperity» of the state and society, events. The problem of state building is a significant debatable issue in the history of state formation and law-making for the period from 1917 to 1921. Nationalization has always been and is a political tool. Nationalization has always been and is a political tool. Nationalization became a revolutionary slogan for the prosperity of the state as a whole, seen as the only option for restoring the war-torn economy, politics, social aspects of society, as well as evolving from the ideas of political autonomy and federation to self-realization. The events that took place from 1917 to 1921 are an all-Ukrainian phenomenon in which the national movement was born and developed, Ukrainian authorities, political parties and public associations were created and carried out, and national culture was revived. Such a sharp political struggle for the independence of Ukraine in 1917 - 1921. left a significant «imprint» not only in the history of Ukraine but also in world history, which incited the national consciousness of the Ukrainian people to the development of nationalism and statehood.

Рассмотрены события, которые происходили с 1917 по 1921 гг., когда украинский народ переживал довольно тяжелые времена, сопровождавшиеся и национальными движениями, сменой органов власти, экономическими кризисами, перехода к разным формам правления и т.д., но все эти преобразования были направлены на установление независимости государства. Дана историко-правовая характеристика формам национализации государственности в период времени с 1917 по 1921 гг. Выделены положительные и отрицательные аспекты их отношения, которые можно применить при введении партнерских отношений между полицией и общественностью, деятельность которых направлена ​​на повышение уровня противодействия уголовным правонарушениям и охране правопорядка.
Forms of national statehood of Ukraine in 1917 - 1921
Новіченко, А. Форми національної державності України в 1917 - 1921 роки / Новіченко Андрій // Європейські перспективи. - 2021. - № 4. – С. 26-33. - DOI: 10.32782/EP.2021.4.4.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; державність; statehood; государственность; націоналізація; nationalization; национализация; державне будівництво; state construction; государственное строительство